Case Report: Idiopathic calvarial hyperostosis and concurrent nasal discharge in a 22-week-old Staffordshire bull terrier - Travail, Victoria; Moreno-Aguado, Beatriz; Motta, Claudio; Garcia, Beatriz; Kelly, Darren (Frontiers in Veterinary Science, 2025)
A 22-week-old Staffordshire bull terrier presented with acute onset of bilateral mucopurulent nasal discharge and lethargy. Clinical examination revealed pyrexia and pain upon palpation of the head, accompanied by marked asymmetrical swelling. Computed tomography (CT) of the head showed severe thickening of multiple calvarial bones with periosteal reaction, with small defined areas of fluid accumulation and contrast enhancement of the osteopenic areas. There was mild thickening of the mucosa of the frontal sinuses suggestive of sinusitis, fluid in the left nasal passage, choanae, and nasopharynx. Histological examination of biopsies of the bone revealed periosteal reaction with fibrosis, neutrophilic and histiocytic inflammation, and necrosis. Culture yielded negative results. The dog was diagnosed with idiopathic calvarial hyperostosis and medically managed with methadone, paracetamol, and meloxicam. At recheck 10 days later, all clinical signs had resolved except for mild persistence of skull asymmetry. To the authors’ knowledge, this is the first report of idiopathic calvarial hyperostosis in a Staffordshire bull terrier. The presence of bilateral purulent nasal discharge represents a novel clinical sign not previously reported.